Orientação sexual: concepções e práticas pedagógicas dos docentes da Escola Municipal Gleba Pernambuco em Inhangapí-PA - CERQUEIRA, Monica Maciel (2019)
This work has the theme "Sexual Orientation: Conceptions and pedagogical practices of the teachers of the Gleba Pernambuco Municipal School in Inhangapí - PA". It has as justification, since the theme must be worked in the process of teaching and learning by the teachers, in a transversal and interdisciplinary way. We emphasize as problematic the absence of a work in the school that contemplates the theme so that the teachers can develop different practical activities. The general objective is: To analyze the procedures and methodologies used by teachers in the development of the subject in their pedagogical practices. The research is of the bibliographic type, of qualitative character, where data was collected with the support of a questionnaire, as an aid instrument for the semi-structured interview technique. We develop in the 1st Chapter: The History of Sexuality in the course of time with the items: The history of sexuality in Brazil and Sex education in Brazil. In the second chapter, it deals with the sexual education in the vision of the family; reflecting on the concepts and definition of: sexuality and sex concepts and definition of sexuality Freudian, Sexual education at school as prevention in teenage pregnancy; The importance of school sex education in combating STD-AIDS and others. It is also characterized the school, and presents the analysis and result of data, subsidized by the authors: Adorno (1969), Arruda (2009), Bandura (2008), Baltar (1996), Barroso , Carla (2012), Camargo (1999), Costa (2000), Cunha (2006), Domingos (2010), Egypt (2003), Figueiró (2006), Foucault (1988/2015), Freud ) and others. It is concluded that, faced with so many social changes that we are experiencing, the school needs to expand in its spaces, debates to guide the students and parents, on the theme from the most diverse perspectives.